Fear of judgement and women's physical (in)activity experiences. (May 2022) - Seal, Emma; Nicholson, Matthew; McNeil, Nicola; Stukas, Arthur; O'Halloran, Paul; Randle, Erica
There is a significant body of research that examines the antecedents and consequences of population-level disparities in physical activity engagement. However, there are still vast gendered inequalities with women missing out on the associated health benefits of physical activity compared to men. The purpose of this study is to foster a deep understanding of the 'fear of judgement' experienced by physically inactive women to develop policy and practice that can attend to this issue. The theory of reflexive embodiment, rooted in the interactionist tradition, provides the theoretical underpinning for the work as it highlights how women's bodies are influenced by the gaze of others. Results demonstrate that women feel judged for the way their bodies look and move during exercise, for prioritising physical activity over family duties, and that these sensations are influenced by the networks of people in activity spaces. The impact of judgement affects women's mental and physical wellbeing. It leads to the cessation of physical activity, creates worries about restarting various forms of activity and shapes how and where women undertake exercise.